2012
DOI: 10.4236/ajps.2012.311191
|View full text |Cite
|
Sign up to set email alerts
|

Rolling Circle Amplification Is More Sensitive than PCR and Serology-Based Methods in Detection of <i>Banana streak virus</i> in <i>Musa</i> Germplasm

Abstract: Banana (Musa sp.) is a popular and important crop among many communities in East Africa. Banana production is however threatened by the wide-spread banana streak disease (BSD), caused by Banana streak virus (BSV). The success of BSV management is inherently coupled to the availability of a sensitive indexing method. In this study, the sensitivity of three BSV detection techniques: rolling circle amplification (RCA), immunocapture PCR (with degenerate and Gold finger primers) and standard PCR was compared. A se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 11 publications
1
4
0
Order By: Relevance
“…Results of this study confirmed previous works (James et al, 2011;Wambulwa et al, 2012) that RCA is very reliable to detect episomal BSV, as the sequenceindependent nature of RCA can selectively amplify circular and not linear (integrated) DNA. RCA specifically amplified the genome of episomal BSV present in 'Nanicão Jangada' (Table 1, Figure 2).…”
supporting
confidence: 79%
“…Results of this study confirmed previous works (James et al, 2011;Wambulwa et al, 2012) that RCA is very reliable to detect episomal BSV, as the sequenceindependent nature of RCA can selectively amplify circular and not linear (integrated) DNA. RCA specifically amplified the genome of episomal BSV present in 'Nanicão Jangada' (Table 1, Figure 2).…”
supporting
confidence: 79%
“…RCA would also aid in the detection and identification of new badnaviruses. The RCA combined with RFLP was successfully employed in the detection of BSV species and FBV-1 [ 55 , 73 , 77 ]. A combination of immunosorbent electron microscopy (ISEM), IC-PCR, RCA, virus purification, Southern and in situ hybridizations, and complete sequencing of the virus genome may be required to elucidate the precise identification of the type of sequences present.…”
Section: Diagnosis and Cure Of Badnavirusesmentioning
confidence: 99%
“…Multiplex immunocapture PCR (M-IC-PCR) and rolling circle amplification (RCA) have been developed for the detection of BSV genomes [ 72 , 73 , 104 ]. RCA was more sensitive than PCR and serology-based methods in the detection of BSV [ 77 ]. Selvarajan et al [ 62 ] developed serological-based detection of BSMYV using the recombinant virus-associated protein encoded by ORF II, which is very specific to each species of BSV.…”
Section: Virus Characterizationmentioning
confidence: 99%
“…RCA is a sequence-independent approach that is often used in the laboratory for the amplification of circular DNA virus genomes, thus overcoming the shortcoming of primer dependency in PCR for the amplification of viruses with a circular DNA genome [ 33 , 38 , 39 ]. The RCA technique has been used successfully for the study of several other circular DNA viruses such as sweet potato leaf curl virus [ 40 ] and beet curly top virus [ 41 ] of the family Geminiviridae , and BSV [ 39 , 42 ] and fig badnavirus 1 [ 34 ] of the family Caulimoviridae. It was proposed that RCA could be used for the specific detection of episomal forms of yam badnaviruses [ 30 ].…”
Section: Introductionmentioning
confidence: 99%